2019
DOI: 10.1002/ptr.6535
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nettle (Urtica dioica) supplementation on the glycemic control of patients with type 2 diabetes mellitus: A systematic review and meta‐analysis

Abstract: Type 2 diabetes mellitus (T2DM) is a major health problem, worldwide, that is associated with increased morbidity and mortality. Several randomized controlled clinical trials (RCTs) have investigated the effect of nettle (Urtica dioica) supplementation on markers of glycemic status in patients with T2DM, with conflicting results. Therefore, the present study assessed the effect of nettle on some glycemic parameters in patients with T2DM. A comprehensive search was conducted in PubMed, Scopus, Cochrane Library,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 54 publications
(90 reference statements)
0
23
1
Order By: Relevance
“…Therefore, different parts of this plant may have different applications for functional food production due to its valuable nutritional and biological composition [4][5][6][7]. In particular, aerial parts of the nettle are good sources of polyphenols [8][9][10] and pigments [11,12] with different pharmacological and medicinal properties [13][14][15]. Dried nettle extract has already been used as commercially formulated food supplement that may have positive effects on reducing osteoarthritis symptoms [16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, different parts of this plant may have different applications for functional food production due to its valuable nutritional and biological composition [4][5][6][7]. In particular, aerial parts of the nettle are good sources of polyphenols [8][9][10] and pigments [11,12] with different pharmacological and medicinal properties [13][14][15]. Dried nettle extract has already been used as commercially formulated food supplement that may have positive effects on reducing osteoarthritis symptoms [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen of these studies were excluded because they included an abstract ( N = 5) or a protocol ( N = 1) only, were not published in English ( N = 1), had inappropriate exposures ( N = 2) or outcomes ( N = 1), or did not provide updated data ( N = 2). As a result, 50 systematic reviews and meta‐analyses were included in the final analysis (Figure 1; Amir Shaghaghi et al, 2013; Askari et al, 2019; Azhdari et al, 2019; Chen et al, 2020; Fatahi et al, 2019; Ghaedi et al, 2019; Ghaedi et al, 2020; Glisic et al, 2018; Gui et al, 2016; Hadi et al, 2018, 2020; Hadi, Pourmasoumi, Mohammadi, et al, 2019; Hadi, Pourmasoumi, Najafgholizadeh, et al, 2019; Hallajzadeh et al, 2020; Hamedifard et al, 2019; Han et al, 2019; Hasani et al, 2019; Hemati et al, 2020; Hernández‐García et al, 2019; Heshmat‐Ghahdarijani et al, 2020; Karimian et al, 2019; Khorshidi et al, 2020; Li et al, 2014, 2015, 2020; Maierean et al, 2017; Mansour‐Ghanaei et al, 2018; Mohammadi, Hadi, et al, 2019; Mohammadi, Ramezani‐Jolfaie, et al, 2019; Ostadmohammadi et al, 2019; Pourmasoumi et al, 2018, 2020; Rahmani et al, 2019; Rahmani et al, 2020; Ricci et al, 2010; Ried, 2016; Rocha et al, 2019; Sahebkar, 2014; Sahebkar, Simental‐Mendía, et al, 2016; Sahebkar, Soranna, et al, 2016; Salehi‐Sahlabadi et al, 2020; Serban et al, 2015; Shekarchizadeh‐Esfahani et al, 2020; Taku et al, 2010; Ursoniu et al, 2018; Zhang et al, 2020; Zhang, Yuan, et al, 2016; Zhang, Liu, et al, 2016; Zhu et al, 2017; Ziaei et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, its main application is related to treatment of benign prostatic hyperplasia. In addition, some studies have described benefits for U. dioica extract for management of diabetes complications [ 34 , 57 , 89 ]. More recently, it was demonstrated that supplementation with plain U. dioica led to body weight loss in mice that received a high-fat diet, via modulation of genes related to lipid and glucose metabolism [ 33 ].…”
Section: Discussionmentioning
confidence: 99%